2020
DOI: 10.1002/ajmg.b.32814
|View full text |Cite
|
Sign up to set email alerts
|

Why does age of onset predict clinical severity in schizophrenia? A multiplex extended pedigree study

Abstract: Schizophrenia has substantial variation in symptom severity, course of illness, and overall functioning. Earlier age of onset (AOO) is consistently associated with negative outcomes and yet the causes of this association are still unknown. We used a multiplex, extended pedigree design (total N = 771; 636 relatives from 43 multigenerational families with at least 2 relatives diagnosed with schizophrenia and 135 matched controls) to examine among the schizophrenia relatives (N = 103) the relationship between AOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Musket et al [40] also identified shared genetic effects between age at onset and negative symptom severity in patients with schizophrenia. Additional evidence supports the idea that early onset of schizophrenia is moderately heritable [39,40] and that a familial component exists in the relationship between cognitive performance and psychosis [41,42]. Thus, the presence of an early age of onset and a low pIQ may reflect a specific neurodevelopmental course within psychotic disorders [43].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Musket et al [40] also identified shared genetic effects between age at onset and negative symptom severity in patients with schizophrenia. Additional evidence supports the idea that early onset of schizophrenia is moderately heritable [39,40] and that a familial component exists in the relationship between cognitive performance and psychosis [41,42]. Thus, the presence of an early age of onset and a low pIQ may reflect a specific neurodevelopmental course within psychotic disorders [43].…”
Section: Discussionmentioning
confidence: 94%
“…Lack of insight has been a variable with state and trait characteristics (these latter ones associated with schizophrenia and particularly early onset) that could have a role in the persistence of negative symptoms [75,76]. Musket et al [40] also identified shared genetic effects between age at onset and negative symptom severity in patients with schizophrenia. Additional evidence supports the idea that early onset of schizophrenia is moderately heritable [39,40] and that a familial component exists in the relationship between cognitive performance and psychosis [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier onset is often associated with a poorer outcome [37]. Promotion of good mental health, prevention, and early intervention before/at the onset of mental disorders improve outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this is the first study aiming to identify predictive factors of negative symptoms dimensions separately. Previous studies have reported a young age of onset, early onset of illness, cognitive symptoms, general psychopathology as predictors of the broad domain of negative symptoms (Fujimaki et al, 2018, Cuesta et al, 2020, Musket et al, 2020.…”
Section: Discussionmentioning
confidence: 99%